Constantinople: capital of Byzantium - Harris, Jonathan (Hambledon Continuum, 2007)
The city of wonders -- Founding fathers -- Defence -- Palaces and power -- Churches and monasteries -- 'Two thirds of the wealth of this world' -- Democracy -- The beginning of the end -- The ruin of Byzantine Constantinople -- Epilogue: Byzantine Constantinople today